Oxidative costs of cooperation in cooperatively breeding Damaraland mole-rats - Mendonça, Rute (Proc Biol Sci, 2020)
Within cooperatively breeding societies, individuals adjust cooperative contributions to maximize indirect fitness and minimize direct fitness costs. Yet, little is known about the physiological costs of cooperation, which may be detrimental to direct fitness. Oxidative stress, the imbalance between reactive oxygen species (by-products of energy production) and antioxidant protection, may represent such a cost when cooperative behaviours are energetically demanding. Oxidative stress can lead to the accumulation of cellular damage, compromising survival and reproduction, thus mediating the trade-off between these competing life-history traits. Here, we experimentally increased energetically demanding cooperative contributions in captive Damaraland mole-rats (Fukomys damarensis). We quantified oxidative stress-related effects of increased cooperation on somatic and germline tissues, and the trade-off between them. Increased cooperative contributions induced oxidative stress in females and males, without increasing somatic damage. Males accumulated oxidative damage in their germline despite an increase in antioxidant defences. Finally, oxidative damage accumulation became biased towards the germline, while antioxidant protection remained biased towards the soma, suggesting that males favour the maintenance of somatic tissues (i.e. survival over reproduction). Our results show that heightened cooperative contributions can ultimately affect direct fitness through oxidative stress costs, which may represent a key selective pressure for the evolution of cooperation.